Evaluation of Student Character Development in the Pancasila Student’s Profile Project Using the CIPP Model - Ardiansyah, Vendra (PPSDP International Journal of Education, 2024)
This research aims to evaluate the implementation of the Pancasila Student’s Profile Strengthening Project using the CIPP evaluation model (Context, Input, Process, Product). The study was conducted at SMP Negeri 3 Penukal Utara and involved 98 students and 13 teachers. Data collection methods included observation, questionnaires, interviews, and documentation. The evaluation results indicate that the implementation of the Pancasila Student’s Profile Strengthening Project was overall successful. In terms of context, there was a strong readiness and support from the school and community. Regarding input, it was found that the curriculum, teacher training, and resource allocation were adequate. However, in the implementation process, there is room for improvement, particularly in the quality of classroom interactions and teaching methods. Product evaluation shows the achievement of character education goals and positive impacts on student behavior. The research conclusion emphasizes the program’s success in implementing Pancasila values and shaping student character, although it still requires attention and improvement.